Erg Power vs. On-Water Power - Kleshnev, V. (BioRow, 2019)
The question is answered: How does a rower`s erg score correlate with their in-boat power? 47 university rowers in six crews were tested in the same eight instrumented with the BioRow telemetry system: 34 women (averaging 1.73m, 67.9kg, where one rower was tested twice and her best performance data was used), and 13 lightweight men (1.79m, 74.0kg,). The standard BioRow test protocol was used consisting of a single 2000m piece with increasing rate steps (RBN 2013/03). Each rower`s season-best 2k erg was obtained from the head coach of the squad. A very high correlation r=0.814 was found between the erg power and average power production in the boat (Fig.1). This means 66.3% - two thirds of power variation in a boat is explained by the erg scores of the rowers.